Abnormal gait and motor cortical processing in drug‐resistant juvenile myoclonic epilepsy. Issue 2 (5th January 2023) - Maidan, Inbal; Yam, Mor; Glatt, Sigal; Nosatzki, Shai; Goldstein, Lilach; Giladi, Nir; Hausdorff, Jeffrey M; Mirelman, Anat; Fahoum, Firas
Abstract: Background: Juvenile myoclonic epilepsy (JME) is characterized by generalized seizures. Nearly 30% of JME patients are drug‐resistant (DR‐JME), indicating a widespread cortical dysfunction. Walking is an important function that necessitates orchestrated coordination of frontocentral cortical regions. However, gait alterations in JME have been scarcely investigated. Our aim was to assess changes in gait and motor‐evoked responses in DR‐JME patients. Methods: Twenty‐nine subjects (11 JME drug‐responder, 8 DR‐JME, and 10 healthy controls) underwent a gait analyses during usual walking and dual‐task walking. Later, subjects underwent 64‐channel EEG recordings while performing a simple motor task. We calculated the motor‐evoked current source densities (CSD) at a priori chosen cortical regions. Gait and CSD measures were compared between groups and tasks using mixed model analysis. Results: DR‐JME patients demonstrated an altered gait pattern that included slower gait speed ( p  = .018), reduced cadence ( p  = .003), and smaller arm‐swing amplitude ( p  = .011). The DR‐JME group showed higher motor‐evoked CSD in the postcentral gyri compared to responders ( p  = .049) and both JME groups showed higher CSD in the superior frontal gyri compared to healthy controls ( p  < .011). Moreover, higher CSD in the superior frontal gyri correlated with worse performance in dual‐task walking ( r  > |–0.494|, p  < .008). Conclusions: These alterations in gait and motor‐evoked responses in DRE‐JME patients reflect a more severe dysfunction of motor‐cognitive neural processing in frontocentral regions, leading to poorer gait performance. Further studies are needed to investigate the predictive value of altered gait and cortical motor processing as biomarkers for poor response to treatment in JME and other epilepsy syndromes. Abstract : Patients with JME demonstrated abnormal gait pattern compared to healthy controls, which were even more accentuated in drug‐resistant patients. Furthermore, we found different spatial distribution of motor evoked potentials that strongly correlated with the abnormal gait measures. Overall, our results suggest that detailed gait assessment should be sought after in JME patients, as it possible reflects motor‐cognitive neural integrity and patients' responsiveness to medications.